Farelo de arroz desengordurado desfitinizado na alimentação de frangos de corte - Karkow, Ana Kátia (2011)
Abstract: The objective of this dissertation was to evaluate dephytinizated defatted rice bran for feeding broilers under performance parameters, carcass yield, tibiae resistance and apparent digestibility of protein, calcium and phosphorus. We used 576 male Cobb one day old broiler chicks. The experimental design was completely randomized, with four treatments (basal diet - DB; basal diet with addition of 10% defatted rice bran - FAD; basal diet with addition of 10% defatted dephytinizated rice bran - FADD; basal diet with the addition of 10% defatted rice bran treated with phytase - FADFIT) with 6 replicates of 24 birds each. Growth performance of the lot was not significantly different (P>0.05) among different treatments, as well as carcass yield. The tibiae of birds fed diets with added FADD showed less resistance to breakage compared with those fed the DB (P<0.05). Apparent protein digestibility was higher in birds fed FADD (P<0.05) when compared to those receiving FAD. It can be concluded that the addition of 10% of FADD in the diet, does no damage and has benefits in the digestibility of the protein, allowing the incorporation of this ingredient in feed for broilers.